A Comparative Study of Tianzhu White Yak's Blood Copper with Yak's in Other Sites of Tibetan Plateau - Cao, Jun-Hu; Zhao, Xin-Quan; Xie, Jian-Min; Li, Jin-Ping; Feng, Bing-Fu; Zhang, Bo (Asian Journal of Chemistry, 2012)
One hundred and ten individually male yaks which lived in eleven sites around Qinghai Tibetan Altiplano were used to determine the whole blood concentrations of trace elements (Cu, Cr, Mn). Yak were stratified by regions to 11 sites. The eleven areas or treatments is Tibet (including Yadong, Rikeze, Dangxiong, Shannan), Qinghai (including Yushu, Maqin, Dari), Gansu (including Tianzhu and Sunan), Xinjiang (including Heshuo, Yiwu), respectively. The date of experiment showed that the trace elements concentrations of whole blood range were copper 0.585-0.755 μg/mg, chromium 17.315-20.877 μg/mg and manganese 0.216-0.264 μg/mg, respectively. Results indicate that the copper concentrations in whole blood of white yaks lived in Tanzhu were specific lower than they were on whole blood of yak which lived in other areas else. Analysis of correlation between copper and other trace elements in plasma from yaks also found a significant positive correlations. The correlations between plasma copper, chromium and manganese were r = 0.282 and 0.254 (p < 0.01), respectively.